The Art of the Leader - Cohen W. A. (Englewood Cliffs Prentice Hall, 1990)
The author of 16 business books, Cohen here contends that, with proper training, almost anyone can become a leader. Defining the difference between management and leadership, he recommends ``influence strategies and how and when to use these. To illustrate his points, Cohen quotes liberally from four-star generals and admirals, offering a veritable anthology of slogans, maxims, catchphrases and historical anecdotes. He also discusses staff relations, motivation and fostering teamwork within an organization, basing his advice on sports and military principles. Much of the guidance provided is self-evident common sense cloaked in managerial and psychological jargon.
Keywords: 005 .